Arabic Learning Program at Mahad Al-Irsyad through Muhadatsah and Khitabah - Muzadi, Narul Hasyim; Zaman, Badrus; Al-Ghotnini, Raid (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2024)
As an Islamic educational institution, Ma’had Al-Irsyad has a strong reputation in Arabic language teaching and da'wah. Arabic language learning programs are designed to give students practical experience in actively using Arabic in various communication contexts while deepening their understanding of Islamic teachings. This study aims to describe how Arabic language learning programs develop Arabic language skills and to understand the impact of the unique learning environment at Ma’had Al-Irsyad on students' ability to master the language actively. The results of this study indicate that the Arabic language learning program at Ma’had Al-Irsyad Batu City includes the al-muhadatsah al-'usbu'iyah (weekly conversation) and the khitabah (public speaking) programs. For the muhadatsah program, participants can develop confidence in speaking, expand their vocabulary, and improve their understanding of Arabic grammar, strengthening their ability to interact in social and professional situations that require oral communication in Arabic. The Khitabah program has a positive impact in increasing participants' confidence and courage to perform in public. The learning syntax, namely: a) direct learning model, consisting of orientation, presentation, structured practice, guided practice, and independent practice. b) The presentation learning model consists of advanced organizer presentation, task presentation, and cognitive process reinforcement.